Case for diagnosis - Andre Lencastre; Joana Cabete; Maria Margarida Apetato (Sociedade Brasileira de Dermatologia, 2013)
An 83 year-old man was observed for an 8 year-long pruritic, erythematous plaque of the left axilla. He had been continuously medicated with topical antifungals and steroids with occasional symptomatic relief, but with disease progression. After a clinical and histological diagnosis of Extramammary Paget's Disease, a total excision with wide margins was performed. He remains disease-free 12 months after surgery. We report this rare presentation of Extramammary Paget's Disease on a male patient.